The Study of Children's Speech in World Linguistics - Ergashev Shoxrux, (European Journal of Life Safety and Stability (2660-9630), 2024)
This article talks about the importance of studying children's speech in different cultures and languages, its main directions, field-related methodologies, and environmental factors related to this process in world linguistics. In addition, information is provided about the linguistic environment of children, their speech patterns and ways of forming knowledge of different languages. The topic is analyzed and further enriched by the researches of linguists.